2008
DOI: 10.1007/s12041-008-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ageing since Darwin

Abstract: In the late 19th century, the evolutionary approach to the problem of ageing was initiated by August Weismann, who argued that natural selection was more important for ageing than any physiological mechanism. In the mid-twentieth century, J. B. S. Haldane, P. B. Medawar and G. C. Williams informally argued that the force of natural selection falls with adult age. In 1966, W. D. Hamilton published formal equations that showed mathematically that two 'forces of natural selection' do indeed decline with age, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…In most circumstances, reproduction that occurs earlier in life will have a larger effect on fitness and on the rate of population growth than reproduction that occurs later in life (Rose et al 2008). Thus, under the antagonistic pleiotropy theory of aging, beneficial mutations early in life will be favored even if they cause deleterious effects late in life (Willams 1957).…”
Section: Discussionmentioning
confidence: 99%
“…In most circumstances, reproduction that occurs earlier in life will have a larger effect on fitness and on the rate of population growth than reproduction that occurs later in life (Rose et al 2008). Thus, under the antagonistic pleiotropy theory of aging, beneficial mutations early in life will be favored even if they cause deleterious effects late in life (Willams 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Cowpea seeds are larger than mung beans and support more larvae per seed, such that there is less selection for female avoidance of occupied seeds during oviposition on cowpea relative to mung bean (Tuda and Iwasa 1998;Messina and Karren 2003). If finding and inspecting hosts takes more time in populations adapted to small seeds, chronic association with small hosts may mimic selection for delayed reproduction, which in turn can lead to the evolution of increased lifespan (Rose et al 2008). Decreased lifespan may evolve in our cowpea lines because shifting to this larger host selects for an accelerated reproductive schedule, which causally leads to a shorter adult life through antagonistic pleiotropy, or because a plastic change in the reproductive schedule on Evol Biol (2011) 38:182-196 191 larger seeds (more eggs laid early in life) relaxes selection against late-acting deleterious alleles that reduce lifespan.…”
Section: Convergent Evolution Of Adult Lifespan and The Shape Of The mentioning
confidence: 99%
“…These investigators described that a reduction in food given to juvenile water fleas delayed the start of reproduction, extended the reproductive period, and increased lifespan. In addition to showing that CR extends lifespan in nonmammalian species, Ingle et al (27,28) described, for the first time, a result that would become a general principle in the evolutionary theory of longevity, i.e. genes selected for successful reproduction are linked to longevity (see further explanation on this topic below).…”
Section: -1945: the Forerunners Of Aging Researchmentioning
confidence: 99%
“…Moreover, the evolutionary problem of longevity and aging was solved. Evolutionary theorists had mathematically and empirically demonstrated that longevity was genetically determined from genes that were selected for a reproductive advantage (27,28). Age-related decline in function was due to random events occurring during development and the reproductive phase (58).…”
Section: -Present: the Search For Mechanismsmentioning
confidence: 99%